KOMUNIKASI KEARIFAN LOKAL PEUSIJUK SEBAGAI IDENTITAS DAN CITRA BUDAYA MASYARAKAT ACEH - Mustira, Sheila; Wiryany, Detya (JURNAL LENSA MUTIARA KOMUNIKASI, 2025)
Peusijuk is a cultural heritage of the Acehnese community that embodies deep religious, social, and symbolic values. The background of this study lies in the need to understand peusijuk not merely as a ceremonial ritual, but as a form of cultural communication that contributes to the construction and preservation of Acehnese identity and cultural image. This research aims to explore peusijuk as a form of local wisdom communication that reflects relational identity, shapes cultural imagery, and functions as a medium of social interaction. This study employs a qualitative descriptive method, with data collected through observation, interviews, and documentation. Data analysis was conducted using data reduction techniques, and data validity was ensured through source triangulation. The results show that peusijuk not only strengthens social cohesion within the Acehnese community but also conveys symbolic messages reflecting values such as harmony, gratitude, and blessing. The tradition is capable of adapting to local variations and evolving societal contexts, though it faces challenges from modernization. In conclusion, peusijuk serves as an effective medium of cultural communication that helps maintain local wisdom and reinforces the collective identity of the Acehnese people. Therefore, educational and creative efforts are needed to ensure its relevance and continuity in modern society.